UNDERSTANDING THE PHYSICS OF KAPPA (Κ0): INSIGHTS FROM THE EUROSEISTEST NETWORK - Ktenidou, O.J.; Abrahamson, N.; Drouet, S.; Cotton, F. (Bulletin of the Geological Society of Greece, 2016)
this study we estimate the spectral decay factor κ0 for the EUROSEISTEST array. Site conditions range from soft sediments to hard rock over 14 surface and 6 downhole accelerographs. First, we separate local and regional high frequency attenuation and measure κ0. Second, we use the existing knowledge of the geological profile and material properties to correlate κ0 with different site characterisation parameters (Vs30, resonant frequency, depth-to-bedrock). Third, we use our results to improve our physical understanding of κ0. We propose a conceptual model comprising two new notions. On the one hand, we observe that κ0 stabilises for high Vs values; this may indicate the existence of regional values for hard rock κ0. If so, we propose that borehole measurements may be useful in determining them. On the other hand, we find that material damping may not suffice to account for the total measured attenuation. We propose that, apart from damping, additional site attenuation may be caused by scattering from small-scale profile variability. If this is so, then geotechnical damping measurements may not suffice to infer overall crustal attenuation under a site; but starting with a regional (borehole) value and adding damping, we might define a lower bound for site-specific κ0.